Budget reform politics the design of the appropriations process in the House of Representatives, 1865-1921 - Stewart, Charles Haines (Political economy of institutions and decisions, 1989)
In this 1989 book Charles Stewart analyses the development of the budgetary process in the House of Representatives between 1865 and 1921. The period began with the creation of the House Appropriations Committee and ended with the passage of the Budgetary Accounting Act. Attempts at change were closely related to societal and economic, but also to institutional, developments during this period. Both the electoral system and the national party system, as well as war and other economic crises, impacted upon the budgetary process